Evaluation Of The Child-Friendly City (Kla) Program - Jesika Puteri; Muhalida Zia Ibhar (LPPM STIA Lancang Kuning Dumai, 2023)
The Child-Friendness City Program in Bengkalis Regency has been evaluated using William N. Dunn's 6 criteria: effectiveness, efficiency, adequacy, equity, responsiveness, and accuracy. This evaluation includes policy goals and objectives, financial capabilities and Human Resources (HR), children's safety and needs, distribution of activities, policies, and decrees, and implementation of policy products. This program has two inhibiting factors: community participation and facilities. Children in Law no. 23 of 2002 concerning Child Protection was defined as someone not yet 18. Bengkalis Regency implements the Child-Friendly City program and has met several indicators to obtain this title. However, there were still cases of children conflicting with the law even though this program has been implemented. This evaluation aims to resolve these cases.